(untitled) (Research, Society and Development, 2022)
The economic importance of patent protection has been increasing and more recognized, especially in less technologically developed economies. For these countries, capital-intensive activities, which characterize most technological innovations, are less common, with their innovation production systems heavily based on derived innovation products, such as utility models. The purpose of this article was to discuss the global trend in the behavior of utility model patents according to income levels defined by the World Bank in the period between 2000 and 2018. The main results confirmed strong direct relationships between the demand for utility model patents and lower-middle-income economies. In addition, these economies are also positively impacted by the parallel increase of this type of industrial protection in medium-high economies and are also responsible for the highest productivity rates of MU patent applications. In this context, the importance of a protection system suited to the reality of each country emerges, as a mechanism to guarantee economic progress. In this sense, the utility model patent protection regime, as an alternative for patent protection aimed at smaller and incremental innovations, was, and is being used, a useful tool to promote innovation and economic prosperity in countries.